2014
DOI: 10.17221/73/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

Application of chlorophyll fluorescence performance indices to assess the wheat photosynthetic functions influenced by nitrogen deficiency

Abstract: Nitrogen deficiency influences importantly the plant photosynthetic capacity and crop productivity. Here, we employed the rapid, non-invasive measurements of chlorophyll a fluorescence kinetics for calculation of the integrative fluorescence parameters related to the leaf photosynthetic performance. In pot experiments with winter wheat (Triticum aestivum L.) we cultivated plants during the whole growing period in the soil substrate supplied with four different doses of nitrogen. The leaf nitrogen and chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(58 citation statements)
references
References 25 publications
(22 reference statements)
1
55
0
2
Order By: Relevance
“…In abiotic stress studies (e.g., drought and nitrogen deficiency), the chlorophyll a fluorescence and the derived indices have been successfully used to assess the plant stress conditions [25][26][27]. In this study, chlorophyll a fluorescence was measured with the portable fluorometer "Handy-PEA" (Hansatech, Norfolk, UK).…”
Section: Reference Measurements To Assess the Crop Water Statusmentioning
confidence: 99%
“…In abiotic stress studies (e.g., drought and nitrogen deficiency), the chlorophyll a fluorescence and the derived indices have been successfully used to assess the plant stress conditions [25][26][27]. In this study, chlorophyll a fluorescence was measured with the portable fluorometer "Handy-PEA" (Hansatech, Norfolk, UK).…”
Section: Reference Measurements To Assess the Crop Water Statusmentioning
confidence: 99%
“…It is near to impossible not to evoke the popular Performance Index (PI) of Strasser when discussing the parameters derived from the JIP-test (Silvestre et al, 2014; Zivčák et al, 2014). Recently Kalaji et al (2016) recommended the non-specialist to resort to the PI in the absence of a serious capacity to understand and exploit the other parameters.…”
Section: What Can We Learn From the Parameters Of The Jip-test?mentioning
confidence: 99%
“…Fluorescence ratios (F 740 /F 685 and F 685 /F 525 ) were widely utilized for the estimation of the nitrogen status and for the diagnosis of crop growth because of their simplicity in measurement and interpretation [11,46]. However, studies of Yang Jian et al [47] indicated that these fluorescence ratios were insensitive to the rice LNC.…”
Section: Lnc Estimation Using Reflectance Spectrum and Reflectance + mentioning
confidence: 99%